2021
DOI: 10.3324/haematol.2021.278785
|View full text |Cite
|
Sign up to set email alerts
|

Progress in understanding the biology of nodular lymphocyte-predominant Hodgkin lymphoma

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Many differences distinguish cHL and NLPHL, leading to the consideration of NLPHL as a low-grade B-cell lymphoma. However, as with cHL, GEP demonstrated that the lymphocyte predominant (LP) cells in NLPHL show a strong NFkB activity signature, but this activation is a consequence of different mechanisms than those observed in cHL [ 70 , 71 ].…”
Section: Specificities Of Nodular Lymphocyte Predominant Hlmentioning
confidence: 99%
“…Many differences distinguish cHL and NLPHL, leading to the consideration of NLPHL as a low-grade B-cell lymphoma. However, as with cHL, GEP demonstrated that the lymphocyte predominant (LP) cells in NLPHL show a strong NFkB activity signature, but this activation is a consequence of different mechanisms than those observed in cHL [ 70 , 71 ].…”
Section: Specificities Of Nodular Lymphocyte Predominant Hlmentioning
confidence: 99%